CURCUMIN ACTION AGAINST PRE-CANCEROUS LESION - DR.M.ELUMALAI,; DR. S.BHUMINATHAN,; DR. D. RAMYAA, (International Journal of Pharma and Bio Sciences, 2014)
Oral precancerous lesions are one of the most common lesions present worldwide today. They are usually neglected by the common population when compared to cancerous lesion. However, they also may be extremely fatal which changes as cancer if left untreated at a very initial stage of the lesion. Early detection and treatment gives the best chance for its cure. The detection and diagnosis are currently based on clinical examination, histopathological evaluation. Several medications have been developed over the years for early cure of oral precancerous lesion. The purpose of this article is to review the available curcumin herbal to treat these precancerous lesions.